CONTEMPORARY WOMEN AND RELIGIOUS FUNDAMENTALISM - Vernekar, Sanjyot D Pai (Journal of Dharma, 2001)
Admittedly, issues exclusively relating to women have been receiving considerable attention since the international women's year (1975) and the decade 1975-85'. Groups of experts seeking to study the status of women all over the world' are a familiar sight today. All forms of media are full of reports produced by such committees. By and large, these reports recognise that theoretically women have political and social equality with men.f All civilized societies today claim to have put an end to educational and job discrimination against women. Large numbers of contemporary women enter several important fields of life including law, medicine, politics and other fields which were traditionally considered to be spheres where only men could enter and work until the mid-twentieth century. In the developed societies of today men and women share even child care and other family responsibilities. As a result of various types of feminist movements, women have achieved greater social, economic and political involvement today '. On account of this, the fewer rights and a lower social status thrust on women in the past have been reduced considerably. The industrial age has revolutionized women's traditional roles and caused women to question their status and situation.